Kinematic analysis of javelin throwing in Japnese elite thrower - Koyama, Y.; Nishimura, T.; Miyauchi, I. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The aim of this study was to investigate the kinematic factors of javelin throwing due to improvement of athletic performance in Japanese elite javelin thrower. Methods: Subject of this study was Japanese male elite javelin thrower (Height: 186cm, Weight: 104kg, personal record: 85.96m (2013)) who participated in the 2008 and 2012 Olympic games. He performed Japanese 2nd ranking of 85.96m at the 47th Mikio Oda Memorial international amateur athletic game (Domestically competition) in 2013. Three dimensional analyses of javelin throwing were measured two competitions in japan (91th Japan championship in athletics (2007) and 47th Mikio Oda Memorial international amateur athletic game (2013)). Throwing motion was recorded by two digital video cameras (120Hz) in each competitions. One of the video cameras was placed at the right side of the approach runway, the other one was placed behind the approach runway. Throwing motion was analyzed by using Frame-DIAS V for Windows application (DKH, Japan). In this study, horizontal velocity of wrist, elbow and shoulder in throwing arm were kinematic analyzed in each trials. And also, we calculated in joint angle of elbow in throwing arm and relative horizontal distance of grip position to shoulder joint during javelin throwing. Results: In this study, subject was improved competition result from 2007 to 2013 season. He was competed in the two-time Olympic game and many of the world championship. And also, He had gold medal at the Asian games in 2011 (83.15m). In kinematic factors of javelin throwing in 2013 season, horizontal velocity of each joint was slightly increase after the left foot grounded compared to 2007 season. Elbow joint angle in 2007 season was more flexion from left foot grounded to release than the 2013 season. And also, relative horizontal distance of grip position to shoulder joint in 2013 season was located in backward from right foot to left foot grounded compare to the 2007 season. Discussion: In generally, if flexed elbow from right foot to left foot grounded during javelin throwing, it is not possible to increase the javelin acceleration distance. In 2013 season, elbow joint angle was extended and increased javelin acceleration distance as compared to the 2007 season. From these result, it was considered that javelin throwing performance may affect by movement of the body including elbow joint angle in elite thrower.